EXPRESSIVE ILLOCUTIONARY ACTS TOWORDS AGUS YUDHOYONO’S NEWS IN JAKARTA GLOBE AND THE JAKARTA POTS’S NEWSPAPERS - Humaira Restu Maulidia; Cita Mustika Kusumah; Dien Novita; Teti Sumarni (Universitas Widyatama, 2023)
Understanding the function of socially and culturally aspects play an important role in language learning. People will use a different language in a different context and situation. They will find out with whom, where, when, and in what stages they are talking. Therefore, the context cannot be separated to comprehend an utterance. According to Yule (1996) states that context is the situation surrounding the production of utterance. Furthermore, Leech (1983: 13) in Citraresmana (2015) states that “context is any background of knowledge assumed to be shared by speaker and hearer which contributes to the interpretation of what speaker means by given utterance.” Therefore, this present paper is aimed to find out the expressive illocutionary acts in newspapers from Jakarta Globe and the Jakarta Post about the current issue of Susilo Bambang Yudhoyono’s son which is Agus Yudhoyono who decided to take part in Jakarta gubernatorial election. The newspaper from Jakarta Globe entitled “There's Logic behind Sacrificing Agus Yudhoyono’s Military Career: Former House Speaker” which published on Saturday, September 24, 2016. Besides, the newspaper from The Jakarta Post entitled “SBY’s son’s decision to enter politics regretted: TNI” which published on September 29, 2016. The research objectives are to find the types of expressive illocutionary acts that used in the utterance and to find the similarities of expressive illocutionary acts in both newspaper. Further, this research employs a qualitative approach as suggested by Creswell (2014) and find 14 utterances as the data. The finding of the research showed that there were two types of expressive illocutionary acts that found in the article, protesting and praising. Moreover, both types of the illocutionary acts are found in Jakarta Globe and Jakarta Post